Role of non-active site residues in maintaining New Delhi metallo-β-lactamase-1(NDM-1) function: an approach of site-directed mutagenesis and docking. Issue 4 (9th January 2019) - Ali, Abid; Gupta, Divya; Khan, Asad U
Abstract: New Delhi metallo-β-lactamase-1 (NDM-1) has been known to hydrolyze nearly all β-lactam antibiotics, leading to a multidrug-resistant state. Hence, it is important to study its structure and function in relation to controlling infections caused by such resistant bacterial strains. Mutagenesis is one of the approaches used to explore it. No study has been performed to explore the role of non-active site residues in the enzyme activity. This study includes mutations of three non-active site residues to comprehend its structure and function simultaneously. Three non-active site laboratory mutants of NDM-1 were generated by site-directed mutagenesis. The minimum inhibitory concentrations of cefotaxime, cefoxitin, imipenem and meropenem were reduced by up to 4-fold for these mutants compared with wild-type. The hydrolytic activity of mutants was also found to be reduced. Mutants showed a significant change in secondary structure compared with wild-type, as determined by CD spectrophotometry. The catalytic properties and stability of these mutants were found to be reduced. Hence, it revealed an imperative role of non-active site residues in the enzymatic activity of NDM-1.